2018
DOI: 10.1016/j.appet.2018.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Towards more sustainable food systems. Addressing food waste at school canteens

Abstract: Food Waste is a global significant issue for ethical, environmental and economic reasons, while its management is difficult due to its frequent low visibility. Individual choices and preferences are closely related to the generation of food waste although likely to be modified through education and awareness campaigns. In particular, school canteens are big generators of food waste and, at the same time, provide a great opportunity to improve habits regarding nutrition and education on sustainability, thus imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 42 publications
3
52
0
1
Order By: Relevance
“…A study conducted in primary schools in Barcelona showed a mean discarded weight 21-47 g as plate waste. The lower values were observed where there was an increased awareness of pupils due to two main factors: the inclusion in the students' career eating behaviour and patterns and a very attention of school managers and teachers to sustanaibility [7]. This observation is the main reason to move our project towards the raise of a cultural approach in teachers, pupils and parents.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…A study conducted in primary schools in Barcelona showed a mean discarded weight 21-47 g as plate waste. The lower values were observed where there was an increased awareness of pupils due to two main factors: the inclusion in the students' career eating behaviour and patterns and a very attention of school managers and teachers to sustanaibility [7]. This observation is the main reason to move our project towards the raise of a cultural approach in teachers, pupils and parents.…”
Section: Discussionmentioning
confidence: 89%
“…The differences between canteens with external or internal cooking centers is an interesting argument, because the study in Florida shown more waste when there is an internal cafeteria or an internal cooking center. The study by Darqui et al instead highlight the advantage to have an internal service, if students are involved in the canteen [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the absence of pre‐ordering systems leading to kitchens catering for unknown numbers of pupils, inflexible portion sizes, fixed food combinations, rushed mealtimes and pupils buying cheaper snacks rather than a full meal. Thus, reducing food waste, as well as educating pupils on the issue of food waste, should be a consideration in the development of school food policies (Derqui et al ).…”
Section: Introductionmentioning
confidence: 99%